An experiment on the teachability of oral communication strategies in the English classroom : do they really work on ESL pre-university learners? - Mohd. Ramli, Nur Aziera (2011)

(untitled)
This study seeks to investigate the teachability of oral communication strategy training (OCST) on ESL learners at pre-university level. The issue of teaching communication strategies in the ESL classroom has been controversial over the past few decades. To address this issue, an experiment had been done on the students to investigate if the teaching of communication strategies works on the ESL learners specifically at the university level. In this study, some communication tasks were created in order to motivate students to use English for communication in real situations. Respondents in this study consist of 62 international students of low-proficiency who attended an English course conducted by the Centre for Languages and Pre-University Academic Development (CELPAD) at the International Islamic University Malaysia. The students came from various countries and backgrounds. One class received 14 weeks of OCST and the other served as a control group. Data was collected from the students’ performance in communicative tasks (role-play) and questionnaires. The findings revealed that students in the strategy-training group significantly improved in their oral proficiency using communication strategies.